Selected writings on anarchism and revolution / P. A. Kropotikin ; edited, with an introduction, by Martin A. Miller - Miller, Martin A. (Martin Alan) (1938-); Kropotkin, Piotr Alekseevich (MIT. Political science)
Bibliografía: p. [360]-362. Índices